Object, experience, knowledge in the artwork (Papeles, 2017)
This text aims to take stock of the aesthetic experience produced by the work of art through its moments of object, experience and knowledge. Here it is postulated that knowledge is the moment of synthesis of the aesthetic experience, in which the ineffable moment of the work of art manifests itself as another knowledge (another, no doubt, with respect to discursive and conceptual knowledge). In this regard, the work of art is questioned about aesthetics, but in a special way in the understanding providedby the reflections given by GWF Hegel and Theodor Adorno, in a line of thought that from my own inquiry is inscribed in the problematic of the representation, in a precise manner, in the politics of representation. I make this reflection in the context of a discussion about research-creation within the framework of academic spaces, especially in the universities that teach at the professional and postgraduate levels in the field of arts. This context cannot be lost sight of, even though our arrival to it may be a bit slow. In any case, the road constructs the place of arrival and must provide us with the elements that allow reflection and the postulation of strategies in the field of research-creation.
Keywords: experience; object; knowledge; aesthetics; politics of representation